Optimization of agricultural planting structure in major grain-producing areas based on supply and demand and water resources: A case study of Hebei Province - Wenxue Xia; Jiankang Dong; Bing Zhang; Jingyan Han (Agricultural Water Management)
The misalignment between the water-soil-grain supply and demand system presents a major challenge to the sustainable development of China’s agriculture, and optimizing crop planting structures plays a key role in it. Currently, the dietary patterns of Chinese residents are shifting from subsistence-based to well-being-oriented, evolving from a predominantly “grain and vegetable” structure to a diversified diet incorporating “grain, meat, vegetables, and fruits”. Given the rigid constraints on water resources, addressing how to optimize crop planting structures in Hebei Province while considering multiple objectives remains a critical challenge. This study focused on Hebei Province, analyzing its agricultural planting situation and incorporating the balanced dietary needs of Chinese residents into the “water-soil-grain” planting structure optimization model. Using the NSGA-II algorithm, the study optimized the crop planting structure under two scenarios: water-saving objective and water-efficiency objective. The results revealed the following: (1) The total crop output in Hebei Province increased consistently, while the cultivated land area remained relatively stable. The annual average of total agricultural water use showed a downward trend with an average annual decrease of 1.88 %. (2) In the scenario 1, the grain planting area decreased by 15.88 %, while the fruit planting area increased by 2.09 times, meeting the needs of a low-level balanced diet. In the scenario 2, the planting areas for vegetables and fruits increased while the grain planting area decreased by 10.91 %. That has important implications for the utilization of agricultural water resources and the enhancement of regional food security in water-scarce areas.